Estudo comparativo entre o uso de refervedores e injeção direta de vapor em colunas de destilação - Silva, Rodrigo Orgeda da (2013)
Distillation is a tool for the separation of components that consists in vaporization of a liquid, or a mixture of liquids, followed by immediate condensation of the vapors produced; it may be performed by two main methods. The first method is based on the production of a vapor by boiling the liquid mixture to be separated and condensing the vapors without allowing any liquid to return to the still. There is then no reflux. The second method is based on the return of part the condensate to the still under such conditions that this returning liquid is brought into intimate contact with the vapors on their way to the condenser. Either of these methods may be conducted as a continuous process or as a batch process. The heating of the still can be done in two ways: direct steam injection and use of reboilers. Reboilers are heat exchangers commonly used to provide heat to the bottom of distillation columns industry. They boil the liquid of the bottom of a distillation column to produce vapors which are returned to the still. The aim of this work was to compare three alcohol distillation columns projects, using for the column heater, direct steam injection, partial or total reboiler. First, it was developed mass and energy balances for the cases of direct and indirect heating for the distillation column in a stripping section. Then, it was calculated the variation of the number of plates in both types of heating. With the values obtained by the system of equations, the area of partial and total reboilers was dimensioned. Besides, an analysis of the financial project viability was made. A field research on a plant in operation was undertaken to provide information that helped in the design of reboilers and sustained, more realistically, the final discussion of the advantages and disadvantages of this project. Results about the study of case showed that it is possible to have a reduction of almost 17% of the amount of stillage and 1,8% of the amount of steam. Because there was a decrease in the amount of steam, it was possible estimate the payback time of approximately two years. In this scenario, the partial reboiler proved to be more viable than the total one, since promotes a separation stage, which can increase the efficiency of the column, and has lower cost than the total reboiler. Thus, it can be stated, in both financial and environmental aspects, it is advantageous to carry out the change proposed in this project.